Application of Interpersonal Communication with an Andragogical Approach in Improving the English Competence of Dhuafa Orphans - Lili Musyafa'ah; Abd Latih Bustami; Dzulkarnain Dzulkarnain (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
The english competency of orphan children are not as good as the students who have complete parents. The orphan children have no parents who can accompany them to study and to support them in studying. They are usually shy and afraid to say waht they need to everyone.So the orphan students need to be taught by an approach which can improve their english competency. Quali Interpersonal Surabaya Institution has a programme to the orphan children that can improve their English competency. They are taught by an andragogy approach with interpersonal communication. For that need the existence of research that able to see the result reach by the participants to the program of the application approach with interpersonal communication in English competency achievement. Research conducted to know the result of the application of andragogic approach with interpersonal communication counseling that can improve English competency at Quali International Surabaya institution seen from the process of training the Orphans. And also to describe the participation of participants in the program how to improve english competency by applying the Andragogy approach with interpersonal Communication Counseling in Quali International Surabaya Institution. The main problem to be known in this research that is to increase English competency by self concept, life experiences, learning readiness, learning orientation, need knowledge and motivation. This research used descriptive and qualitative method. The techniques of collecting data used in this research was interview, observations and documentation. The writer can conclude that the English training for increasing competency of the orphans, improvement can be seen from the changes of the learners before and after training orphans independently increase competency seen from indicators  of achievement of the results. They can pass the English competency examination which held by the certification institution in English competency.      Keywords : andragogy approach, interpersonal communication, english competency achiement